Integrative GWAS and eQTL analysis identifies genes associated with resistance to Vibrio harveyi infection in yellow drum (Nibea albiflora) - Huang, Ying; Li, Jiacheng; Li, Wanbo; Han, Fang (Frontiers in Marine Science, 2024)
Vibrio harveyi is a major pathogen in yellow drum (Nibea albiflora) aquaculture, causing significant mortality and economic losses. In this study, using the latest assembled reference genome of yellow drum by our laboratory, we conducted Genome-wide association study (GWAS) analysis on fin tissue DNA from 345 individuals (197 susceptible and 148 resistant). The analysis revealed 24 significant single nucleotide polymorphisms (SNPs) on chromosome 24 within a 217 Kb region. The estimated heritability for all genome-wide SNPs was 0.3578, while the heritability for the 24 significant SNPs was 0.0710. Four candidate genes were identified within this region: Suppressor of Cytokine Signaling 1 (SOCS1), C-type Lectin Domain Family 16A (CLEC16A), Major Histocompatibility Complex Class II Transactivator (CIITA), and Protein Kinase Cβ (PRKCB). Subsequently, expression quantitative trait loci (eQTL) analysis was performed on transcriptome sequencing data from spleen tissues of 78 individuals from the resistant group. On average, each chromosome harbored 49,396 eQTL loci, with an average of 1.3 genes regulated per SNP. Notably, 22.79% of SNPs showed significant associations with the expression of one or more genes. By integrating GWAS and eQTL data, seven SNPs were identified to have significant associations with regulated genes in the eQTL results. All seven SNPs were found to target the same gene, namely Zinc Finger Protein yd23210 in yellow drum. This study provides genetic markers and candidate genes for molecular breeding of yellow drum against V. harveyi infection, offering insights into the molecular immune mechanisms and potential pathways for genetic improvement of disease resistance traits in this species.